State of Emergency in the Republika Srpska: Legal Regulation - Markovic, Goran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The legal regime of the state of emergency is regulated very poorly in the Republika Srpska and in Bosnia and Herzegovina in general. It is necessary to carry out a detailed positive legal and comparative legal analysis of this legal regime, with the aim of formulating proposals for amending of the Constitution and laws of the Republika Srpska. Their goal would be greater legal certainty and more detailed and meaningful legal regulation, which would reduce opportunities for abuses of state power and endangering human rights. The authors first of all analyze the constitutional provisions on the declaration of a state of emergency, the functioning of state institutions and the restriction of human rights during its duration. The authors come to the conclusion that the constitutional provisions are so lapidary, that the state institutions, especially the executive, have wide possibilities for regulation of the state of emergency and the exercise of state power during its duration, even relatively wide possibilities of limiting human rights. The authors believe that this is extremely inappropriate legal solution. Therefore, they make a series of proposals for amendments to the Constitution of the Republika Srpska, so that the legal regime of the state of emergency would be as fully regulated as possible, which would significantly reduce the possibilities of abuse of state power. In the second part of the paper, the authors analyze in detail the legal and sub-legal provisions related to the state of emergency, as well as the practice of the Constitutional Court of the Republika Srpska. They point out that the by-laws, enacted during the state of emergency, were largely in conflict with constitutional and legal norms, thereby violating the principles of constitutionality and legality.